Artificial Intelligence for Healthcare Fraud Prevention: A Systematic Literature Review - Ridwan Ridwan; Dian Arlianty (The ASEAN Journal of Military and Preventive Medicine, 2026)
The purpose of the study was to identify the methods used to detect fraud in health services using artificial intelligence. Methods: This research was conducted using a systematic review through searching for articles using the keywords “artificially intelligent” and “fraud Healthcare” and then entered into the Scopus journal search engine based on secondary data on the publish or perish application. 8. Then the selection of journals and articles is based on the suitability title theme. The article aims to detect health services fraud by using artificial intelligence. Results: The findings from the twelve articles reviewed indicate that fraud can be prevented and detected by using an information technology system embedded in the application for filing claims in health services as a tool for auditors in conducting audits. Health insurers/insurers must adopt increasingly sophisticated machine learning methods as part of their fraud prevention system to proactively identify instances of fraud.